Metastatic Medullary Thyroid Carcinoma Mimicking a Primary Soft Tissue Sarcoma of the Shoulder: A Case Report - Putri, Syifa Azizah; Kiki Akhmad Rizki; Rupita Endangena Sitanggang (HM Publisher, 2026)
Background: Medullary thyroid carcinoma (MTC) is a rare neuroendocrine malignancy accounting for 1-5% of thyroid cancers. While often presenting with cervical lymphadenopathy, distant metastasis to bone and soft tissue mimicking a primary sarcoma is exceptionally rare. This report details a case of MTC where the primary diagnostic challenge was a massive, destructive shoulder mass. Case presentation: A 58-year-old woman presented with a disabling, 20 cm mass in her left shoulder, progressively enlarging over two years. The patient also noted a 30-year history of a stable, asymptomatic neck lump. Magnetic Resonance Imaging (MRI) revealed a large, hypervascular, destructive mass obliterating the scapula and invading surrounding musculature, with a radiological differential diagnosis of a primary soft tissue sarcoma. Laboratory investigation, however, revealed a massively elevated serum calcitonin (>2000 pg/mL) and carcinoembryonic antigen (CEA) (180 ng/mL). A CT-guided core biopsy of the shoulder mass, initially suspected to be a sarcoma, was negative for all sarcoma markers. Instead, it was strongly positive for neuroendocrine (Synaptophysin, Chromogranin A) and thyroid-specific (TTF-1, PAX-8) markers, as well as definitive MTC markers (Calcitonin, CEA). This confirmed the diagnosis of metastatic MTC. Staging was completed as pT3a pN1b M1. The patient underwent total thyroidectomy with bilateral central and left modified radical neck dissection, followed by planned palliative resection of the shoulder metastasis and systemic therapy with a selective RET inhibitor. Conclusion: This case highlights a critical diagnostic pitfall. Metastatic MTC can present as a massive soft tissue neoplasm mimicking a primary sarcoma. In such cases, a systematic diagnostic approach combining serum biomarkers (Calcitonin, CEA) with a comprehensive immunohistochemical panel is essential to establish the correct diagnosis and initiate appropriate, life-extending targeted therapy.